Therapeutic Effects of PSL-Loaded PLGA-PEG-PLGA NPs in Allergic Contact Dermatitis Model Mice - Ryo Fujisawa; Ryuse Sakurai; Takeshi Oshizaka; Kenji Mori; Akiyoshi Saitoh; Issei Takeuchi; Kenji Sugibayashi (Molecules)
This study focused on the poly(DL-lactide-co-glycolide)-block-poly(ethylene glycol)-block-poly(DL-lactide-co-glycolide) (PLGA-PEG-PLGA) triblock copolymer, which was recently reported as a novel material for polymeric nanoparticles to replace poly(DL-lactide-co-glycolide) (PLGA) as a drug carrier for prednisolone (PSL), and aimed to evaluate the efficacy of PSL-loaded PLGA-PEG-PLGA nanoparticles (NPs) against allergic contact dermatitis (ACD). PSL-loaded PLGA-PEG-PLGA NPs were prepared using the nanoprecipitation method, and their particle size distribution and mean particle size were measured using dynamic light scattering. 1-Fluoro-2,4-dinitrobenzene (DNFB) was used to create a mouse model of contact hypersensitivity (CHS). PSL-loaded PLGA-PEG-PLGA NPs were administered before sensitization with DNFB, and the therapeutic effect was evaluated by quantifying intracutaneous TNF-α and IL-4 levels suing ELISA. When PSL-loaded PLGA-PEG-PLGA NPs were administered before sensitization, TNF-α expression and IL-4 statements were significantly lower in the PSL-loaded PLGA-PEG-PLGA NP group than in the non-treated group. No significant difference was observed between the PSL-loaded PLGA-PEG-PLGA NP and PSL-loaded ointment groups, even though the steroid dose was 40 times lower than in the PSL-containing ointment. These results suggest that PSL-loaded PLGA-PEG-PLGA NPs may have a better effect in the treatment of ACD than PSL-loaded PLGA NPs.